ESI-MS assay of M. tuberculosis cell wall antigen 85 enzymes permits substrate profiling and design of a mechanism-based inhibitor. - Barry, C; Backus, K; Barry, C; Davis, B (2011)
Mycobacterium tuberculosis Antigen 85 enzymes are vital to the integrity of the highly impermeable cell envelope and are potential therapeutic targets. Kinetic analysis using a label-free assay revealed both mechanistic details and a substrate profile that allowed the design and construction of a selective in vitro mechanism-based inhibitor.